A comparative study of in vitro gastrointestinal digestion of three strategic edible oils. Issue 7 (21st July 2022) - Chabni, Assamae; Bañares, Celia; Reglero, Guillermo; Torres, Carlos F.
Abstract: Three strategic edible oils, that is, olive oil, microalgae oil, and shea butter, with a significantly different composition of fatty acids (FA), have been studied in a static in vitro digestion model to evaluate the rate of hydrolysis, bioaccessibility, and micellar phases formed in the process. Lipid composition of each phase and how the lipids are distributed in the different phases have been obtained using this in vitro digestion model. We demonstrate that the composition in FA and the physical properties of the oil are the key factors determining the distribution of lipids in the different phases. The fastest rate of hydrolysis was observed for olive oil and the highest triacylglycerol conversion was attained for shea butter. In contrast, the most abundant precipitate phase was obtained for shea butter, which also produces the highest co‐crystallization of cholesterol among the three edible oils studied. This study reveals that digestibility of edible oils is directly related with the initial rate of hydrolysis.